2022
DOI: 10.1109/access.2022.3190978
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analysis on Anti-Analysis Techniques in Real-World Malware

Abstract: To dynamically identify malicious behaviors of millions of Windows malware, anti-virus vendors have widely been using sandbox-based analyzers. However, the sandbox-based analysis has a critical limitation that anti-analysis techniques (i.e., Anti-sandbox and Anti-VM techniques) can easily detect analyzers and evade from being analyzed. In this work, we study on anti-analysis techniques used in real-world malware. First off, to measure how many Windows malware exhibits anti-analysis techniques, we collect anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…In line with recent research detailing the success of DBI tools in countering malware evasive behavior 19,23,[32][33][34] Pin allocates on the heap. Pinvm.dll makes a copy of the malware executable along with the injected Peekaboo instrumentation code in the code cache 70 .…”
Section: Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…In line with recent research detailing the success of DBI tools in countering malware evasive behavior 19,23,[32][33][34] Pin allocates on the heap. Pinvm.dll makes a copy of the malware executable along with the injected Peekaboo instrumentation code in the code cache 70 .…”
Section: Methodssupporting
confidence: 77%
“…However, there is an existing body of research that have developed methods to defeat the anti-instrumentation probes performed by malware 19,21,30,33,34 . In contrast to the 80% and 99% of malware samples that used anti-analysis techniques, identi ed above, Kim, et al 32 and Polino, et al 33 found that approximately 16% and 15% of malware used anti-instrumentation techniques. This indicates the evasive techniques used by malware authors are not focused on DBI but rather virtualization, debuggers, and sandboxes.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several studies ( Shijo & Salim, 2015 ; Darshan & Jaidhar, 2019 ; Yoo et al, 2021 ) stated that dynamic analysis offers more reliable detection capabilities than static analysis. On the other hand, malware authors use immediate evasion techniques as a defense against dynamic analysis ( Kim et al, 2022 ). By analyzing 45,375 malware samples, Galloro et al (2022) concluded that the use of evasion mechanisms has increased among malware by 12% over the past ten years, and 88% of malicious software can perform new evasion behaviors rather than the older ones.…”
Section: Introductionmentioning
confidence: 99%